2018
DOI: 10.1590/1413-785220182606202125
|View full text |Cite
|
Sign up to set email alerts
|

Are Traumatologists Treating Osteoporosis to Prevent New Fractures in Brazil?

Abstract: Objectives:To determine the proportion of traumatologists who investigate osteoporosis in elderly patients with fractures and recommend secondary prevention of osteoporotic fractures.Methods:We distributed questionnaires to 244 physicians attending the 2015 Brazilian Congress of Orthopedic Trauma. We determined the respondents’ profiles and assessed how they investigated and treated osteoporosis in elderly patients with fractures.Results:Overall, 32% of the respondents reported that their knowledge level regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
5
0
1
Order By: Relevance
“…These findings are worrisome and demonstrate that the treatment of osteoporosis in patients after fracture, despite the numerous publications warning about the subject in the literature, remains less than ideal. ( 5 ),( 7 ),( 10 ),( 12 ),( 13 ),( 17 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings are worrisome and demonstrate that the treatment of osteoporosis in patients after fracture, despite the numerous publications warning about the subject in the literature, remains less than ideal. ( 5 ),( 7 ),( 10 ),( 12 ),( 13 ),( 17 …”
Section: Discussionmentioning
confidence: 99%
“…( 2 ),( 5 ), ( 6 ), ( 7 ), ( 8 ), ( 9 ), ( 10 However, the lack of diagnostic accuracy and guidance of appropriate osteoporosis treatment remain high, even in patients who have already had a first osteoporotic fracture. ( 5 ),( 7 ),( 10 ), ( 11 ), ( 12 ), ( 13 …”
Section: Introductionmentioning
confidence: 99%
“…Neste presente estudo, dos 31 pacientes diagnosticados com osteoporose, 19 faziam suplementação de cálcio e vitamina D, dois apenas de Cálcio, um apenas de Vitamina D, nenhum fazia tratamento farmacológico específico e nove não faziam suplementação e tratamento farmacológico específico. Isso demonstra que mais pacientes deveriam realizar o tratamento adequado da osteoporose com o intuito de evitar complicações graves, como novas fraturas e deformidades secundárias, dor crônica e perda da independência, conforme também observado em outros estudos 20 .…”
Section: Discussionunclassified
“…Despite the impact of osteoporosis and fragility fractures in Brazil, these authors highlighted that 80% of patients with fragility fractures are not evaluated or treated for osteoporosis or fall prevention to reduce secondary fractures. Of interest, Zamboni et al showed that less than 50% of orthopedic surgeons regularly investigated and performed secondary prevention against osteoporotic fractures after treating an elderly patient with a fracture [45] . Finally, Brazil's Ministry of Health expenditures on drugs to treat osteoporosis represent approximately 10.9% of the overall total spending on high-cost medications [46] …”
Section: Introductionmentioning
confidence: 99%
“…Of interest, Zamboni et al showed that less than 50% of orthopedic surgeons regularly investigated and performed secondary prevention against osteoporotic fractures after treating an elderly patient with a fracture. [45] Finally, Brazil's Ministry of Health expenditures on drugs to treat osteoporosis represent approximately 10.9% of the overall total spending on high-cost medications. [46] …”
Section: Introductionmentioning
confidence: 99%